Marketing management - making an impression in the market - S, Pasha (Journal of Management and Science, 2020)
Everybody has an inkling what marketing management is all about, today. However,few people still think that it encompasses the function of sales only. The reality is far away from the scenario. Marketing Management identifies the various opportunities in the market and then comes up with various strategies to utilize the opportunities further.The term can be a bit ambiguous, so it is better to explain it this way. Marketing Management smoothens the process of spreading the information about the products and services to the target market. It also includes some important steps, like planning,organization, direction, and co-ordination.